School meals and the nutrition of schoolchildren. Issue 3 (September 1975) - Cook, J; Altman, D G; Jacoby, A; Holland, W W; Elliott, A
Abstract : The contribution of school meals to the nutrition of 778 primary and secondary schoolchildren attending schools in Kent was assessed using information collected during a survey made in 1968-70 which included a weighed diet record, a socioeconomic questionnaire, and a medical examination. Younger children, those from larger families, those without fathers, and those whose mothers worked were more likely to take school meals. Significantly more children from lower social classes and without fathers received them free. School meals made an important contribution to the nutrition of schoolchildren. Children who took them had higher weekday lunchtime nutrient intake during term-time. Children in lower social classes, larger families, and without fathers who took school meals obtained a higher proportion of their weekday intake of nutrients from lunchtime than other children. This applied in particular to nutrients important for growth. School meals consumed by children in the study broadly met the standard set by the Department of Education and Science. The mean energy and protein content of school meals consumed in the study was slightly lower and the mean fat content higher than the standard set for the meal. The mean sugar content was about one-third higher than the suggested amount of sugar to be included in a school meal. There was no evidence that children who took school meals were taller, heavier, had greater skinfold thickness, or were more likely to be assessed as obese than other children.